Mechanochemical synthesis of N-salicylideneaniline: thermosalient effect of polymorphic crystals - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nangia, Ashwini (IUCRJ, 2017)
Polymorphs of the dichloro derivative of N-salicylideneaniline exhibit mechanical responses such as jumping (Forms I and III) and exploding (Form II) in its three polymorphs. The molecules are connected via the amide N-H center dot center dot center dot O dimer synthon and C-Cl center dot center dot center dot O halogen bond in the three crystal structures. A fourth high-temperature Form IV was confirmed by variable-temperature single-crystal X-ray diffraction at 180 degrees C. The behaviour of jumping exhibited by the polymorphic crystals of Forms I and III is due to the layered sheet morphology and the transmission of thermal stress in a single direction, compared with the corrugated sheet structure of Form II such that heat dissipation is more isotropic causing blasting. The role of weak C-Cl center dot center dot center dot O interactions in the thermal response of molecular crystals is discussed.
Keywords: crystal design; crystal engineering; Halogen bonding; hydrogen bonding; intermolecular interactions; materials science; mechanochemistry; polymorphism

Thermomechanical effect in molecular crystals: the role of halogen-bonding interactions - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nanubolu, Jagadeesh Babu; Nangia, Ashwini (IUCRJ, 2017)
The design and synthesis of mechanically responsive materials is interesting because they are potential candidates to convert thermal energy into mechanical work. Reported in this paper are thermosalient effects in a series of halogen derivatives of salinazids. The chloro derivative, with higher electronegativity and a weaker inter-halogen bond strength (Cl center dot center dot center dot Cl) exhibits an excellent thermal response, whereas the response is weaker in the iodo derivative with stronger I center dot center dot center dot I halogen bonding. 3,5-Dichlorosalinazid (Compound-A) exists in three polymorphic forms, two room-temperature polymorphs (Forms I and II) and one high-temperature modification (Form III). The transformation of Form I to Form III upon heating at 328-333 K is a reversible thermosalient transition, whereas the transformation of Form II to Form III is irreversible and nonthermosalient. 3,5-Dibromo- (Compound-B) and 3-bromo-5-chloro(Compound-C) salinazid are both dimorphic: the Form I to Form II transition in Compound-B is irreversible, whereas Compound-C shows a reversible thermosalient effect (362-365 K). In the case of 3,5-diiodosalinazid (CompoundD) and 3,5-difluorosalinazid (Compound-E), no phase transitions or thermal effects were observed. The thermosalient behaviour of these halosalinazid molecular crystals is understood from the anisotropy in the cell parameters (an increase in the a axis and a decrease in the b and c axes upon heating) and the sudden release of accumulated strain during the phase transition. The dihalogen salinazid derivatives (chlorine to iodine) show a decrease in thermal effects with an increase in halogen-bond strength. Interestingly, Compound-B shows solid-state photochromism in its polymorphs along with the thermosalient effect, wherein Form I is cyan and Form II is light orange.